Testemunho(s): o que é um testemunho para a psicanálise? - Barbará, Cibele Lopes (2017)
Testimony is not a term originally from psychoanalysis; it comes from several fields of knowledge, especially the legal and religious realms/domains. Over time, this term has participated more effectively in other areas, such as psychology, history, philosophy, sociology, arts and, finally, literature. Until the 19th century, what prevailed as a concept of testimony was much more a juridical sense, related to denouncement: an expression of an incontestable truth or its transgression. It was also linked to a way of asserting and attesting faith in a religious sense. According to scholars, the concept has changed and expanded from the moment humanity has experienced an imperious sequence of extreme and violent situations. Testimony, then, gained strength and became a way of resistance, treatment and possibility of transmission as violence, oppression and the decline of the public space became more and more conspicuous; confronting hegemonic discourses and truths. Thus, while studying this concept in various areas of knowledge, this paper proposes to investigate what testimony means for psychoanalysis. In order to obtain some answers to this question, some essential grounds were used: the notion of trauma and traumatic event; repetition and causality; speech act and truth